Pengaturan dan Penegakan Hukum Pedagang Kaki Lima di Kota Denpasar - I Ketut Cahaya Rai Siwi; I Wayan Arthanaya; Luh Putu Suryani (Jurnal Preferensi Hukum, 2021)
Although unlike big cities in Indonesia where the control of street vendors (PKL) is much highlighted by the local government to maintain cleanliness and public order, Denpasar City should start taking into account the presence of street vendors (PKL). For this reason, it is very important to regulate, organize and enforce the law for street vendors (PKL) so that there is order and firmness in its implementation. The purpose of this study is to analyze the regulation of street vendors in Denpasar City and the law enforcement of street vendors in Denpasar City. The type of research used in this research is normative legal research using primary and secondary legal materials. The collection of legal materials is done by reading, researching, understanding and analyzing books or literature, legal provisions, essays, magazines or other forms of information which are then analyzed systematically. The results of the study indicate that the regulation of street vendors in Denpasar City is regulated in the Denpasar City Regulation Number 2 of 2015 concerning PKL. The scope of regulation includes structuring and empowering street vendors. Law enforcement for street vendors includes Preventive Efforts which include providing suggestions or solutions to find vacant land owned by residents who have not been utilized, Counseling by Satpol PP officers. Repressive efforts include actions to stop violations of regional regulations in addition to waiting for the leadership's decision, in this case the mayor's decision and violators of regional regulations to be investigated directly by the PPNS for further processing in the Minor Crime Court